2020
DOI: 10.3389/fnut.2020.00144
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom Bulgaria inquinans Modulates Host Immunological Response and Gut Microbiota in Mice

Abstract: We aimed to determine the prebiotic impact of Mushroom Bulgaria inquinans (BI) on the host immune response and gut microbiota. Male C57BL/6 mice were fed a diet supplemented with 0, 1, or 2% BI for 4 wks. Compared to mice fed with a control diet (0% BI), mice fed with 1 or 2% BI had an increase of T cell proliferation from the spleen, but such change was not found between 1 and 2% BI treated mice. Also, BI at 2% increased the production of IL-2 of splenocytes stimulated with T-cell mitog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Another study has demonstrated that egg white peptides significantly increase the relative abundance of Candidatus_Saccharimonas and inhibit the production of proinflammatory cytokines (Ge et al, 2021). Sang et al (2020) reported that the mushroom Bulgaria inquinans reduces the diversity of the gut microbiota and downregulates the abundance of Candidatus_Saccharimonas and that Candidatus_Saccharimonas is positively correlated with several cytokines (IL-2, IL-4, IL-10, and IFN-γ). Therefore, despite some unclear mechanisms, Candidatus_Saccharimonas might be associated with inflammation and the host immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has demonstrated that egg white peptides significantly increase the relative abundance of Candidatus_Saccharimonas and inhibit the production of proinflammatory cytokines (Ge et al, 2021). Sang et al (2020) reported that the mushroom Bulgaria inquinans reduces the diversity of the gut microbiota and downregulates the abundance of Candidatus_Saccharimonas and that Candidatus_Saccharimonas is positively correlated with several cytokines (IL-2, IL-4, IL-10, and IFN-γ). Therefore, despite some unclear mechanisms, Candidatus_Saccharimonas might be associated with inflammation and the host immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a recent study by Li et al [2021], which indicates that the application of different mushrooms, such as Lentinula edodes, Hericium erinaceus, Grifola frondosa, Ganoderma lucidum, positively affects gut microbiota. This has been validated by using experimental animals fed with Bulgaria inquinans; after a course of treatment, the status of their gut microbiota has been significantly improved [Sang et al, 2020]. Among the identified compounds from mushrooms, non-digestable carbohydrates had a profound impact on the gut microbiota, leading to its restoration in individuals suffering from dysbiosis [Ma et al, 2021].…”
Section: Sensory and Nutritional Evaluation Of Cookies With C Gambosamentioning
confidence: 91%
“…Pre-biotic Mushroom, Bulgaria inquinans (BI) was assessed in male C57BL/6 mice to investigate its impact on gut microbiota. Mice received BI (1 or 2%) for 4 weeks, and the results indicated the decreased diversity of gastrointestinal bacteria, increased abundance of Faecalibaculum and Parabacteroides , and decreased abundance of Allobaculum and Rikenella ( 52 ). A study showed that moderate intake of red wine polyphenols could regulate gut microbiota composition in patients with metabolic syndrome, with significantly increased the number of Bifidobacterium, Lactobacillus , and butyrate-producing bacteria ( Faecalibacterium prausnitzii and Roseburia ) in faeces ( 41 ).…”
Section: Effects Of Pre-biotics On Gut Microbiota and Immune Functionmentioning
confidence: 99%
“…Pre-biotic Mushroom BI was assessed in male C57BL/6 mice to investigate its impact on the host immune response. The results showed that 1 and 2% BI intervention could stimulate the proliferation of T cells from the spleen, and 2% BI could even increase IL-2 production in splenocytes, consequently influencing the peripheral and mucosal immune systems ( 52 ). In a randomised, controlled study, polyphenol supplementation reduced plasma levels of IL-8 in pre-hypertensive volunteers ( 63 ).…”
Section: Effects Of Pre-biotics On Gut Microbiota and Immune Functionmentioning
confidence: 99%